Prinsip dan Praktik Konsep Ar-Rasikhun dalam Hubungan Internasional - Barka Alhudaebi Nawawi (SOSMANIORA: Jurnal Ilmu Sosial dan Humaniora, 2025)
In the context of international relations which are often characterized by conflict and injustice, this research explores the concept of Ar-Rasikhun, which refers to individuals who have deep understanding and wisdom, as a value framework for creating a more ethical, just and peaceful global order. The Ar-Rasikhun concept emphasizes main principles such as universal justice, wisdom-based diplomacy, and tolerance, all of which are rooted in Islamic teachings. Using a qualitative approach based on literature study and normative analysis, this research examines how the Ar-Rasikhun concept can be operationalized in modern diplomacy, multilateral conflict resolution, and the formation of a more humane foreign policy. The findings of this research indicate that the application of Ar-Rasikhun principles is not only relevant in overcoming existing global challenges, but also offers an alternative paradigm that can enrich international relations theory by emphasizing the integration of moral values ​​in diplomacy and international policy. This research contributes to academic discourse by providing a new, more holistic and transformative perspective, and encouraging closer cross-cultural cooperation and sustainable peace. These findings also underline the importance of integrating Islamic values ​​in the formation of a more inclusive and just global order for all humanity. This research also explores the potential of the Ar-Rasikhun concept to provide practical guidance in building more constructive international relations, with a focus on resolving global problems that are more sustainable, inclusive, and based on moral principles that can be accepted by various cultures and civilizations.